Management Of Hazardous And Toxic Waste at PKU Muhammadiyah Hospital Surabaya in 2024 - Fani Rida Wanti; Ferry Kriswandana; Ernita Sari; Setiawan; Ts. Seow Ta Wee (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Hospitals, as healthcare service facilities, generate hazardous and toxic waste. Inadequate management can cause health problems both within the hospital environment and in the surrounding community. This study aims to examine the management of hazardous and toxic waste generated by PKU Muhammadiyah Hospital Surabaya.This research uses a descriptive method by collecting primary and secondary data. The subjects in this study are those responsible for the management of hazardous and toxic waste. The data obtained are then analyzed descriptively using the CIPP evaluation method.The context evaluation of hazardous and toxic waste management based on interviews and observations falls into the good category, while the input, process, and product evaluations based on interviews also fall into the good category. However, based on observations, they fall into the sufficient category. This is because several CIPP evaluation variables have not fully met the assessment criteria. It is hoped that the results of this evaluation can be used as feedback to improve the quality of hazardous and toxic waste management at PKU Muhammadiyah Hospital Surabaya.Based on the research results, it can be concluded that the management of hazardous and toxic waste at PKU Muhammadiyah Hospital Surabaya generally complies with Ministry of Health Regulation Number. 2 of 2023. However, its implementation is not yet optimal, as it is adjusted to the hospital's conditions and capabilities. It is recommended that the hospital improve and upgrade the facilities and infrastructure for hazardous and toxic waste management.